Efektivitas Penerapan Absensi Elektronik Dalam Meningkatkan Disiplin ASN Di Kantor Kecamatan Batuputih Kabupaten Kolaka Utara Provinsi Sulawesi Tenggara - Syafaruddin Syafaruddin; Ambo Masse; Khaeriyah Khaeriyah; Baso Arisandi; Nurasia Natsir (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2022)
This study aims to see the effect of the effectiveness of electronic attendance (finger print) on employee discipline, both in terms of attendance level, convenience and comfort in the attendance process and the application of electronic attendance (finger print) in making it easier for superiors to see employee discipline both in terms of attendance, as well as employee discipline. The results of the study show that the application of finger print attendance has increased employee work discipline, seen from the achievement of targets after the application of finger print attendance has been achieved, where it is known that there are still many employees who are disciplined at work such as arriving on time to the office. Adaptability, employees already understand the procedures regulations for using finger print attendance and being able to adjust from manual attendance to finger print attendance due to previous trials. Job satisfaction for employees is good because of additional employee income (TPP). While the responsibilities of the employees have progressed but not maximized, because there are still employees who leave the office after filling in absences for personal needs. has not increased, there are still many employees who come late to the office. This study discusses the effect of finger print absences on employee discipline. This research is motivated by the problem of the level of punctuality of employees when entering and leaving work, so that it becomes an interesting phenomenon to study. This type of research is qualitative research. Data collection techniques used in this study through interviews, observation, and documentation.